2017
DOI: 10.1113/ep086145
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non‐linear contributions to oxygen transport and utilization during moderate random exercise in humans

Abstract: What is the central question of this study? The pulmonary oxygen uptake (pV̇O2) data used to study the muscle aerobic system dynamics during moderate-exercise transitions is classically described as a mono-exponential function controlled by a complex interaction of the oxygen delivery-utilization balance. This elevated complexity complicates the acquisition of relevant information regarding aerobic system dynamics based on pV̇O2 data during a varying exercise stimulus. What is the main finding and its importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 60 publications
(167 reference statements)
0
26
0
Order By: Relevance
“…In support of recent findings (Beltrame and Hughson, 2017a,b; Beltrame et al, 2017a), the purpose of this study was to describe in detail the computation of the mean normalized gain ( MNG ) and to test its consistency to characterize the trueV˙O2 kinetics during random exercise in humans. The MNG will be validated against the time-domain approach, and checked for intra-subject consistency by applying multiple PRBS protocols on different days and times of the day.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…In support of recent findings (Beltrame and Hughson, 2017a,b; Beltrame et al, 2017a), the purpose of this study was to describe in detail the computation of the mean normalized gain ( MNG ) and to test its consistency to characterize the trueV˙O2 kinetics during random exercise in humans. The MNG will be validated against the time-domain approach, and checked for intra-subject consistency by applying multiple PRBS protocols on different days and times of the day.…”
Section: Introductionmentioning
confidence: 74%
“…The PRBS protocol (Figure 1B) was generated by a digital shift register with an adder module feedback (Bennett et al, 1981; Hughson et al, 1990; Beltrame and Hughson, 2017b) (Figure 1A). The target Ẇ (reached after <1.5 s of transition following a modification of the ergometer controller) was 25 or 100 W, and the cadence was maintained at ≈ 1 Hz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intramuscular phosphocreatine kinetics (Rossiter et al, 1999), de-oxygenated haemoglobin kinetics (DeLeroy et al, 2003;MacPhee et al, 2005), and muscle blood flow kinetics (MacPhee et al, 2005) have all been processed using the monoexponential model. However, a recent publication by Beltrame and Hughson (2017) has indicated that the de-oxygenated haemoglobin signal is nonlinear during dynamic exercise. It therefore seems relevant to research that the kinetic response of these metabolic and physiological functions should also be reinvestigated.…”
Section: Reassessment Of Ventilation Threshold and V̇o 2maxmentioning
confidence: 99%